‘With Mike Hunt I Have Travelled Over the Town:’ the Norms of ‘Deviance’ in Sub-respectable Nineteenth-Century Song - C. M. Jackson-Houlston (Cahiers Victoriens et Edouardiens)
Raymond Williams’s model of competing dominant, emergent and residual ideologies implies a linear progress from one to the other. It obscures the existence of the sort of ‘deviant’ ideology that runs concurrently with the dominant. This, which I would call ‘submerged’ ideology, fulfils much of the function of Bakthin’s carnival, as a semi-licensed refuge for what is insufficiently contained by the dominant discourse of the day. This paper demonstrates the existence of such a submerged discourse through an analysis of the structure and content of the popular songs of song-and-supper clubs of the middle third of the nineteenth century. These are deliberately subversive through their parody of established song models and tunes, and this paper explores the relation of this supposed ‘deviance’ to the respectable gender ideology of the period.